INTERNALISASI HADIS KASIH SAYANG DALAM MEWUJUDKAN SOCIAL INTEREST DI ERA DISRUPSI - Aan Aji Prasetyo (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Problems raised by technological advances have an impact on the creation of a social order that is uprooted from its roots. The order of values that has long been practiced by society, has gradually faded and in time will disappear. In this context, society has faced a moral crisis. To restore these old values, it is necessary to revive the behaviors that are the main source of social capital by reactivating social interest. However, social interest also has vulnerabilities, so we need another element that can be used as a substitute for this attitude. Therefore, this research offers the concept of compassion as a new form of caring in reviving the morale of society that has increasingly faded. For this reason, this research uses a thematic hadith method, with the aim of collecting hadiths that explain compassion in a comprehensive analysis to find the moral messages contained. This research concludes that compassion can be manifested in many forms which indicate that every Muslim is encouraged to respect, respect and be tolerant of others through the manifestation of compassion and loving attitude. This attitude will give birth to concern among humans in the wider community. In relation to moral formation, the use of traditions about compassion is far more effective in reawakening social concerns in the community so that moral values in the era of disruption are still maintained. As a theological basis, the hadith provides a stronger impetus in creating new community relations in the context of modern society, so that technological progress can be balanced with the progress and development of moral values in society.